Improving the recovery of phenolic compounds from spent coffee grounds by using hydrothermal delignification coupled with ultrasound assisted extraction. (August 2020) - Arauzo, P.J.; Lucian, M.; Du, L.; Olszewski, M.P.; Fiori, L.; Kruse, A.
Abstract: This study focuses on the extraction of phenolic compounds from spent coffee grounds by coupling hydrothermal delignification with ultrasound assisted extraction. The hydrothermal treatment was carried out at three different temperatures (200 °C, 230 °C and 260 °C) and two residence times (1 h and 3 h). The ultrasound assisted extractions were performed onto dry hydrochars and slurry fraction, prior treated with three solvents: water, methanol and a water-methanol mixture. The results show that ultra sound assisted extraction applied to the hydrochars using methanol as a solvent lead to the highest extraction of total phenolic content (11.7–20.3 mg GAE/mg of dry sample). The hydrothermal process conditions strongly affect the following extraction: the mildest the delignification process conditions, the highest the extraction of phenols from hydrochar. The hydrochars show also good energy properties in terms of fuel ratio (0.3–0.7), energy yield (83.0–95.2%) and HHV values (28.5–33.2 MJ/kg) and this is promising for their usage as solid biofuels. Highlights: Hydrothermal delignification (HDL) converts coffee spent grounds into hydrochars. The Higher Heating Values up to 28.5 MJ/kg were found for the hydrochars. At 260 °C and 3 h, FC content is 2.4 times greater than in initial feedstock. Ultrasound assisted extraction is an ecologic and fast method for phenol extraction.